Myosin XI-K is involved in root organogenesis, polar auxin transport, and cell division - Abu-Abied, Mohamad (Journal of experimental botany, 2018)
The interplay between myosin- and auxin-mediated processes was investigated by following root development in the triple myosin knockout mutant xi-k xi-1 xi-2 (3KO). It was found that the 3KO plants generated significantly more lateral and adventitious roots than the wild-type plants or the rescued plant line expressing functional myosin XI-K:yellow fluorescent protein (YFP; 3KOR). Using the auxin-dependent reporter DR5:venus, a significant change in the auxin gradient toward the root tip was found in 3KO plants, which correlated with the loss of polar localization of the auxin transporter PIN1 in the stele and with the increased number of stele cells with oblique cell walls. Interestingly, myosin XI-K:YFP was localized to the cell division apparatus in the root and shoot meristems. In anaphase and early telophase, XI-K:YFP was concentrated in the midzone and the forming cell plate. In late telophase, XI-K:YFP formed a ring that overlapped with the growing phragmoplast. Myosin receptors MyoB1 and MyoB2 that are highly expressed throughout the plant were undetectable in dividing cells, suggesting that the myosin function in cell division relies on distinct adaptor proteins. These results suggest that myosin XIs are involved in orchestrating root organogenesis via effects on polar distribution of auxin responses and on cell division